Comparative study between debris flow of wide-gentle and narrow-steep channel based on numerical simulation and prevention measures (Journal of Nepal Geological Society, 2018)
Along the Duwen freeway in the Wenchuan earthquake area, there are two main types of debris flow channels, that is, wide-gentle channel and narrow-steep channel. The wide-gentle channel has the feature of gentle longitudinal slope, large mean width and catchment area. Whereas the narrow-steep one generally shows opposite features with narrow longitudinal slope, small mean width and catchmentarea. During the heavy rainfall, these channels are subject to large-scale debris flows due to huge amount of earthquake-induced collapsing and sliding materials. With field investigation on the formation conditions and development characteristics in the Taoguan and the Mozi gullies, we analysed the resulting impact, burying and blockage to the Duwen freeway and the Minjiang River. The sediment characteristic in the above-mentioned types of debris flow gully was intensively studied. Finally, prevention measures of the debris flow and effectiveness analysis of the treatment were proposed based on the features of the two types of channels.